2022
DOI: 10.1038/s41598-022-10627-9
|View full text |Cite
|
Sign up to set email alerts
|

The nano- and meso-scale structure of amorphous calcium carbonate

Abstract: Understanding the underlying processes of biomineralization is crucial to a range of disciplines allowing us to quantify the effects of climate change on marine organisms, decipher the details of paleoclimate records and advance the development of biomimetic materials. Many biological minerals form via intermediate amorphous phases, which are hard to characterize due to their transient nature and a lack of long-range order. Here, using Monte Carlo simulations constrained by X-ray and neutron scattering data to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 50 publications
1
19
1
Order By: Relevance
“…Indeed, we did not detect any evidence of the presence of Ca–Py entities (clusters) at a nanoscale. A recent study of Clark et al 86 revealed the same kind of model for undoped ACC based on neutrons and X-ray scattering combined to reverse Monte Carlo modelling, with 55 nm-ACC particles containing crystalline anhydrous nanodomains of 2 nm whose cohesion relied on interstitial strongly bound water molecules. Moreover, molecular dynamics simulation assessed the stability of such organisation, in particular when in contact with a water interface.…”
Section: Resultsmentioning
confidence: 96%
“…Indeed, we did not detect any evidence of the presence of Ca–Py entities (clusters) at a nanoscale. A recent study of Clark et al 86 revealed the same kind of model for undoped ACC based on neutrons and X-ray scattering combined to reverse Monte Carlo modelling, with 55 nm-ACC particles containing crystalline anhydrous nanodomains of 2 nm whose cohesion relied on interstitial strongly bound water molecules. Moreover, molecular dynamics simulation assessed the stability of such organisation, in particular when in contact with a water interface.…”
Section: Resultsmentioning
confidence: 96%
“…While it is now generally accepted that amorphous carbonates can be formed with a wide range of hydration levels, the nature of the hydrating water molecules is not well understood, particularly the role of hydrogen bonding in stabilizing amorphous structures. Several previous works have presented atomistic models of hydrated ACC 11,12,16,17,59,62,67,76,77 and AMC. 66,70 We are not aware of any similar reports for ASC.…”
Section: Resultsmentioning
confidence: 99%
“…The nanopores were not found in subsequent CMD 12 and EPSR 62 models, suggesting that homogenous disordered structures could account for all data, although recent work using EPSR and CMD has shown evidence for some degree of nanoporosity. 76,77 To our knowledge, whether ACC (or other amorphous carbonates) feature connected channels is still an open question. But, like many other works, 55,79 we find that open channels do not need to be invoked to reproduce PDF data.…”
Section: Resultsmentioning
confidence: 99%
“…In human bone formation, ACC can also be converted to amorphous calcium phosphate, depending on the availability of exogenous phosphate [ 27 ]. Based on model simulations, it was recently proposed that ACC consists of a hierarchically organized gel-like structure of anhydrous CaCO 3 nanodomains embedded in a matrix of network-like arranged water molecules [ 63 ]. This could explain the stabilization of ACC by polyelectrolytes, both protein and polyP as shown here, which could enter the aqueous channels of this structure.…”
Section: Discussionmentioning
confidence: 99%